Outcomes of Palivizumab Prophylaxis for Respiratory Syncytial Virus Infection in Preterm Children with Bronchopulmonary Dysplasia at a Single Hospital in Korea from 2005 to 2009 - Chang, Seung Gu (The Korean Academy of Medical Sciences, 2010)
This study was performed to evaluate the utilization and outcomes of palivizumab in high risk children born prematurely with chronic lung disease (CLD). A retrospective review of 128 patients was conducted from September 2004 to March 2009 at the Ajou University Hospital. All patients were diagnosed with CLD, were born at ≤35 weeks of gestation, were <2 yr old at the onset of respiratory syncytial virus (RSV) season, and had received medical therapy within six months prior to the RSV season. Fifty-three patients did not receive palivizumab prophylaxis and 75 patients received at least one dose of palivizumab. There were no statistically significant differences between the patients with and without palivizumab prophylaxis with regard to demographic characteristics and risk factors for RSV infection. There were no systemic adverse responses. Compliance with the course of prophylaxis was 92.2%. Hospitalization associated with RSV occurred in 12 cases (22.6%) in the group without prophylaxis and in three cases (4.0%) with prophylaxis. Palivizumab prophylaxis significantly reduced the frequency of RSV-related hospitalization in preterm children with CLD. This is the first retrospective review of palivizumab prophylaxis in Korea. Palivizumab is effective and well tolerated in high risk prematurely born children.